PENGARUH METODE PRAKTIK IBADAH TERHADAP MINAT BELAJAR SISWA DALAM MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI MIS HIDAYATUL MUBTADIIN MUKOMUKO - Tri Handayani, Lilis; Muslihudin, Muhamad (YHMM PUBLISHING, 2025)
This study aims to determine the effect of worship practice methods on students' learning interest in Islamic Religious Education subjects at MIS Hidayatul Mubtadiin Mukomuko. The research employed a quantitative approach with an associative design. Data were collected using a closed-ended Likert-scale questionnaire. The sample was selected using total sampling due to the relatively small population. Data analysis revealed a significant influence of worship practice methods on students' learning interest. Simple linear regression analysis produced the equation Y = 1.25 + 0.72X, with a t-test value of 3.27, which exceeds the critical value of 2.024. The coefficient of determination (R²) was 0.523, indicating that 52.3% of students' learning interest is influenced by the implementation of worship practice methods. These findings suggest that students' active engagement in religious practices can be an effective approach to enhancing learning motivation in religious education. The novelty of this study lies in the application of worship practice as an active and applicable learning strategy in the madrasah context.